The importance of booster vaccination in the context of Omicron wave - Wei, Zichun; He, Jiarui; Wang, Conghui; Bao, Jiaqi; Leng, Taiyang; Chen, Fei (Frontiers in Immunology, 2022)
Omicron (B.1.1.529) was first detected in a sample collected in Botswana on November 11, 2021, and has rapidly replaced Delta as the dominant global variant given the robust transmissibility. Moreover, it displays a lower virulence than other variants. However, the pathogenicity of Omicron appears to be underestimated in view of the increasing levels of herd immunity through natural infection or vaccination. Additionally, the volume of hospitalizations and deaths increase in proportion to the number of cases due to the high transmissibility of Omicron. Therefore, vaccination remains an important public health priority. Notably, a series of important mutations in the Omicron spike protein, especially in the receptor-binding domain and N-terminal domain, appears to be associated with immune escape capacity, reducing the willingness of people to receive vaccines. Herein, we provide an in-depth discussion to assess the effectiveness of the second and third vaccination against Omicron variant. On the one hand, the two-dose vaccination program adopted by many countries is insufficient to prevent Omicron infection given the mutations correlated with immune escape and the decline in vaccine efficacy over time. On the other hand, booster dose significantly increases the protective efficacy against Omicron infection. Most importantly, heterologous third dose vaccination induces a more robust immune response than homologous booster dose. Therefore, under the special background of this pandemic, there is an urgent need to accelerate the third dose of vaccination, especially providing better booster vaccination strategies, to combat emerging Omicron variant.